Rotavirus Reassortant–Induced Murine Model of Liver Fibrosis Parallels Human Biliary Atresia. Issue 4 (11th February 2020) - Mohanty, Sujit K.; Lobeck, Inna; Donnelly, Bryan; Dupree, Phylicia; Walther, Ashley; Mowery, Sarah; Coots, Abigail; Bondoc, Alexander; Sheridan, Rachel M.; Poling, Holly M.; Temple, Haley; McNeal, Monica; et al.
Abstract : Background and Aims: Biliary atresia (BA) is a devastating neonatal cholangiopathy that progresses to fibrosis and end‐stage liver disease by 2 years of age. Portoenterostomy may reestablish biliary drainage, but, despite drainage, virtually all afflicted patients develop fibrosis and progress to end‐stage liver disease requiring liver transplantation for survival. Approach and Results: In the murine model of BA, rhesus rotavirus (RRV) infection of newborn pups results in a cholangiopathy paralleling human BA and has been used to study mechanistic aspects of the disease. Unfortunately, nearly all RRV‐infected pups succumb by day of life 14. Thus, in this study we generated an RRV‐TUCH rotavirus reassortant (designated as T R(VP2, VP4) ) that when injected into newborn mice causes an obstructive jaundice phenotype with lower mortality rates. Of the mice that survived, 63% developed Ishak stage 3‐5 fibrosis with histopathological signs of inflammation/fibrosis and bile duct obstruction. Conclusions: This model of rotavirus‐induced neonatal fibrosis will provide an opportunity to study disease pathogenesis and has potential to be used in preclinical studies with an objective to identify therapeutic targets that may alter the course of BA.